Electrocatalytic Hydrogenation and Deoxygenation of Glucose on Solid Metal Electrodes. Issue 3 (23rd January 2013) - Kwon, Youngkook; Koper, Marc T. M.
Abstract This Full Paper addresses the electrocatalytic hydrogenation of glucose to sorbitol or 2‐deoxysorbitol on solid metal electrodes in neutral media. Combining voltammetry and online product analysis with high‐performance liquid chromatography (HPLC), provides both qualitative and quantitative information regarding the reaction products as a function of potential. Three groups of catalysts clearly show affinities toward: (1) hydrogen formation [on early transition metals (Ti, V, Cr, Mn, Zr, Nb, Mo, Hf, Ta, We, and Re) and platinum group metals (Ru, Rh, Ir, and Pt)], (2) sorbitol formation [on late transition metals (Fe, Co, Ni, Cu, Pd, Au, and Ag) and Al (sp metal)], and (3) sorbitol and 2‐deoxysorbitol formation [on post‐transition metals (In, Sn, Sb, Pb, and Bi), as well as Zn and Cd (d metals)]. Ni shows the lowest overpotential for the onset of sorbitol formation (−0.25 V) whereas Pb generates sorbitol with the highest yield (<0.7 mM cm−2). Different from a smooth Pt electrode, a large‐surface‐area Pt/C electrode hydrogenates glucose to sorbitol from −0.21 V with relatively low current. This emphasizes the importance of the active sites and the surface area of the catalyst. The mechanism to form 2‐deoxysorbitol from glucose and/or fructose is discussed according to the observed reaction products. The yield and selectivity of hydrogenated products are highly sensitive to the chemical nature and state of the catalyst surface.